2016
DOI: 10.1038/nchem.2427
|View full text |Cite
|
Sign up to set email alerts
|

Dissociative electron attachment to CO2 produces molecular oxygen

Abstract: Until recently, it was widely regarded that only one reaction pathway led to the production of molecular oxygen in Earth's prebiotic primitive atmosphere: a three-body recombination reaction of two oxygen atoms and a third body that removes excess energy. However, an additional pathway has recently been observed that involves the photodissociation of CO2 on exposure to ultraviolet light. Here we demonstrate a further pathway to O2 production, again from CO2, but via dissociative electron attachment (DEA). Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 24 publications
0
36
0
Order By: Relevance
“…Specifically, the mechanism differs from that of photochemical interconversion 14 not only in terms of activation (collisional vs. photochemical) but also because the collisional mechanism occurs via a delayed fragmentation of a single CO 2 intermediate, i.e., without visiting the linear COO state. The collisional mechanism also differs fundamentally from that taking place in electron-attachment experiments 17 , where the CO 2 bends spontaneously on the anionic potential energy surface. Instead, the bent CO 2 state is accessed on the neutral surface via collisional energy transfer.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Specifically, the mechanism differs from that of photochemical interconversion 14 not only in terms of activation (collisional vs. photochemical) but also because the collisional mechanism occurs via a delayed fragmentation of a single CO 2 intermediate, i.e., without visiting the linear COO state. The collisional mechanism also differs fundamentally from that taking place in electron-attachment experiments 17 , where the CO 2 bends spontaneously on the anionic potential energy surface. Instead, the bent CO 2 state is accessed on the neutral surface via collisional energy transfer.…”
Section: Discussionmentioning
confidence: 86%
“…Although inaccessible by thermal activation, transitions to electronically excited and anionic states of CO 2 can bend the molecule as a first step to O 2 production. Indeed, pioneering experiments employing VUV photo-excitation 1416 and electron attachment 17,18 have shown that dissociation of CO 2 into C( 3 P) + O 2 (X 3 Σ g − ) is possible, as evidenced by the detection of the complementary atomic C + or C − fragment. Further confirmation of the exotic pathway, however, remained elusive as neutral or ionized O 2 products were not detected.…”
Section: Introductionmentioning
confidence: 99%
“…From all the above-mentioned processes that can be formulated in terms of a complex-valued Hamiltonian, we have chosen to survey a DEA reaction as the rst application of our proposed methodology. DEA is known to play important roles, to a greater or lesser degree, in DNA damage induced by ionizing radiation, 32,33 in the action of radiosensitizing drugs, 33,34 in the chemical evolution of interstellar media 35 and planetary atmospheres, 36,37 in plasma technologies, 38 among many other examples. 19,39 Of particular relevance herein, low energy electrons can very efficiently promote DEA reactions in halogen-containing unsaturated compounds.…”
Section: Introductionmentioning
confidence: 99%
“…9 For example, molecular O 2 has been produced directly from CO 2 in the gas-phase by VUV photolysis and also by dissociative electron attachment with an electron energy between 15.9 and 19 eV. 10,11 Such reaction pathways are not accessible using thermal energy; rather, they require photonic, electronic, or even nuclear excitation means. We show here another unexplored way to drive such reactions by means of gas-surface collisions at hyperthermal incidence energies (60–300 eV).…”
Section: Introductionmentioning
confidence: 99%